EFEKTIVITAS KEBIJAKAN MUSYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) DALAM PROSES PEMBANGUNAN DI KECAMATAN CISARUA KABUPATEN SUMEDANG - Hendrayan, Thalisa Revina (LPPM UNSAP & FISIP UNSAP, 2025)
This study aims to analyze the effectiveness of the Development Planning Deliberation (Musrenbang) policy in the development process in CisaruaDistrict, Sumedang Regency. The research method used is qualitative with a descriptive approach. The focus of the study includes four dimensions of effectiveness based on Budiani's theory, namely program target accuracy, program socialization, program objectives, and program monitoring, as well as inhibiting factors and efforts to improve policy effectiveness based on Fathoni’stheory. The results show that the implementation of Musrenbang in CisaruaDistrict has not been optimal, as indicated by low community participation, lack of socialization, limited access to information, and a mismatch between village proposals and regional development priorities. Furthermore, there is still a lack of clarity in the proposal selection process and inequality of interests among groups. Efforts to enhance policy effectiveness include strengthening the role of the Musrenbang Delegation Forum (FDM), increasing transparency, and providing training and assistance to village communities. The recommendation of this study is the need for improved public education and active community involvement in every stage of the Musrenbang process, as well as strengthened cross-sector coordination to ensure a more inclusive, transparent, and equitable development planning process.